The Role of Intrapreneurship on the Growth of Iron and Steel Manufacturing Companies in Bulawayo, Zimbabwe - Madzikova, Alex; Nani, Gwendoline Vusumuzi (Journal of Economics and Behavioral Studies, 2020)
This study sought to find out the role of intrapreneurship on the growth of iron and steel manufacturing companies in Bulawayo, Zimbabwe. A post-positivist paradigm, a mixed method approach and a cross sectional design were adopted for the investigation. Three hundred and fifteen (315) middle management and supervisory staff drawn from twenty-two (22) iron and steel manufacturing companies in Bulawayo participated. Multiple stratified random sampling and heterogeneous purposive sampling were used to choose two hundred (200) respondents for the quantitative study and eight participants for the qualitative study respectively. Questionnaires and in-depth interviews were the data collecting instruments for quantitative and qualitative data respectively. Quantitative data was analysed using descriptive and inferential statistics and qualitative data was thematically analysed. Findings revealed that innovativeness, proactiveness, and risk taking were the key dimensions of intrapreneurship. Both quantitative and qualitative analyses showed the prominent measures of company growth in the iron and steel manufacturing companies as financial, employee numbers, productivity, and product range. Statistically intrapreneurship was found to be correlated to the growth of the iron and steel manufacturing companies. The study drew the following conclusions. Firstly, intrapreneurship is not a preferred strategy for driving growth in the iron and steel manufacturing companies in Bulawayo. Secondly, financial and product range were identified as the key measures of company growth. Thirdly, company support for intrapreneurship and individual’s intrapreneurial disposition were statistically linked to company growth. The study recommended that companies should motivate and support employees’ innovativeness, proactiveness, and risk taking through ideas, actions and work. Measurement of company growth should be expanded to include qualitative measures.